Optimasi Kecepatan dan Responsivitas Aplikasi Presensi Perkuliahan Berbasis Web melalui Arsitektur Single Page Application - Ali Sadikin; Rahim, Abdul; Siswanto, Agus; Wardani, Muhammad; Ricky Fajar Adiputra (LPPM Universitas Dinamika Bangsa, 2025)
Web-based lecture attendance applications that use Multi-Page Application (MPA) architecture often face speed and responsiveness issues when the number of users increases. This study aims to optimize the attendance application at Universitas Dinamika Bangsa (UNAMA) by implementing Single Page Application (SPA) architecture to improve system access speed and responsiveness. Using the waterfall development method, the results of this study show that SPA implementation is significantly more efficient than Multi-page Application (MPA) architecture in several aspects, including the number of Requests (RC), Transferred File Size (TF), Resources (RS), and Request Duration (RD). For example, the “Home” page on MPA requires 51 requests with a total transfer of 741 kB and a duration of 945 ms, while on SPA it only requires 1 request with a transfer of 5.9 kB and a duration of 187 ms. This proves that the SPA architecture successfully reduces network load and speeds up response time, resulting in a more responsive user experience and efficient use of resources.